Dividend Policy and Equitable Profit Distribution in Islamic Banking Management: A Maqasid al-Shariah Perspective on Shareholder Value Orientation and Stakeholder Welfare - Syahriyah Semaun; Nurul Asia; Muhammad Taqdir (Al-Sharf: Jurnal Ekonomi Islam, 2026)
Dividend policy is one of the strategic decisions in financial management that determines the distribution of corporate profits to shareholders. In Islamic banking, dividend policy is not merely related to financial considerations but must also reflect the principles of justice and public welfare in accordance with the objectives of Maqasid al-Shariah. However, dividend policies in Islamic banking are still predominantly assessed from a shareholder value perspective, while the issue of equitable profit distribution among stakeholders has received limited attention. This study aims to analyze the orientation of dividend policy in Islamic banking, its implications for stakeholder welfare, and the relevance of Maqasid al-Shariah as a framework for evaluating the fairness of profit distribution. The research employs a qualitative approach using a library research method. Data were collected from various literature sources, including scholarly journal articles, academic books, industry reports, and relevant documents, and were analyzed using thematic analysis techniques. The findings indicate that dividend policy in Islamic banking remains predominantly oriented toward shareholder value, positioning shareholders as the primary beneficiaries of profit distribution. Meanwhile, stakeholder theory and the Maqasid al-Shariah perspective emphasize the importance of a more equitable distribution of benefits among all parties contributing to corporate value creation. The study finds that the principles of ?if? al-m?l (protection of wealth), al-‘adl (justice), and ma?la?ah (public welfare) can serve as evaluative instruments to assess the extent to which dividend policy creates a balance between shareholder interests, stakeholder welfare, and corporate sustainability. As a theoretical contribution, this research proposes a Maqasid-Based Dividend Policy Framework as a dividend policy model that integrates financial objectives with Shariah objectives in Islamic banking. The proposed framework also provides practical implications for Islamic banking institutions in designing dividend policies that are sustainable, equitable, and aligned with Shariah objectives as well as stakeholder welfare.